Proceedings of the Ocean Drilling Program, 169 Scientific Results 2000
DOI: 10.2973/odp.proc.sr.169.117.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid fatty acid-derived microbial biomass and community dynamics in hot, hydrothermally influenced sediments from Middle Valley, Juan De Fuca Ridge

Abstract: Phospholipid fatty acids were measured in samples of 60°-130°C sediment taken from three holes at Site 1036 (Ocean Drilling Program Leg 169) to determine microbial community structure and possible community replacement at high temperatures. Five of six samples had similar concentrations of phospholipid fatty acids (2-6 pmol/g dry weight of sediment), and biomass estimates from these measurements compare favorably with direct microscopic counts, lending support to previous microscopic measures of deep sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…In addition, non-culture-dependent 16S ribosomal DNA (rDNA) analysis has been applied to a variety of vent samples (see, e.g., references 11, 14, 15, 23, 29, and 30). However, most of the previous studies were limited to the surfaces of hydrothermal vent systems, while interest in the subsurface habitats of hydrothermal vents (subvents) has been increasing.Only a few subvent microbiological studies have been conducted with sediment, sedimentary rock layers, and igneous rocks from relatively shallow depths (less than 52 m below the seafloor [mbsf]) (4,5,22,26,27). Here, we report the first evidence for the occurrence of a deep-sea subvent biosphere (maximum depth, 128.9 mbsf), by using igneous rock core samples from a back-arc basin hydrothermal vent field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, non-culture-dependent 16S ribosomal DNA (rDNA) analysis has been applied to a variety of vent samples (see, e.g., references 11, 14, 15, 23, 29, and 30). However, most of the previous studies were limited to the surfaces of hydrothermal vent systems, while interest in the subsurface habitats of hydrothermal vents (subvents) has been increasing.Only a few subvent microbiological studies have been conducted with sediment, sedimentary rock layers, and igneous rocks from relatively shallow depths (less than 52 m below the seafloor [mbsf]) (4,5,22,26,27). Here, we report the first evidence for the occurrence of a deep-sea subvent biosphere (maximum depth, 128.9 mbsf), by using igneous rock core samples from a back-arc basin hydrothermal vent field.…”
mentioning
confidence: 99%
“…Only a few subvent microbiological studies have been conducted with sediment, sedimentary rock layers, and igneous rocks from relatively shallow depths (less than 52 m below the seafloor [mbsf]) (4,5,22,26,27). Here, we report the first evidence for the occurrence of a deep-sea subvent biosphere (maximum depth, 128.9 mbsf), by using igneous rock core samples from a back-arc basin hydrothermal vent field.…”
mentioning
confidence: 99%
“…These studies found that mesophilic, thermophilic and hyperthermophilic members of Epsilonproteobacteria, Gammaproteobacteria, Aquificales, Thermococcales and Methanococales were the potentially predominant microbial components in the sub-vent biosphere. In addition, previous studies associated with international scientific ocean drilling projects have also indicated the existence of microbial cells in deep subsurface sedimentary and rocky habitats in the hydrothermal vent systems on the Juan de Fuca Ridge (Ocean Drilling Program (ODP) Leg 139 (Cragg and Parkes, 1994) and 169 (Cragg et al, 2000;Summit et al, 2000) and Integrated Ocean Drilling Program (IODP) Expedition 301 (Lever et al, 2013)) and the Manus Basin (ODP Leg 193 (Kimura et al, 2003)). However, these microbial explorations associated with scientific ocean drilling projects have not successfully provided data on the compositions and functions of potential subseafloor microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…The subseafloor is also one of the most difficult environments to sample. Studies of the subsurface have relied either on sediment cores from deep-sea drilling (9,38,45) or on fluids leaking out of the crust at stable vents or at new sea floor eruption sites (13,23,24,44). Most of what is known about subseafloor microbial communities is based on cultured microorganisms (23,24,44,46,47) and microscopic observations of microbial communities ejected from the subsurface (8,23) Embley, and G. J. Massoth, unpublished data).…”
mentioning
confidence: 99%